Effects Of Fertilizer Fertilizers And Distance To Growth And Production Of Okra (Abelmoschus Eschulentus L.) - Al Machfudz WDP; Fiky Afifih (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to determine the effect of manure and plant spacing on the growth and production of okra plants conducted in Jiken Village, Tulangan District, Sidoarjo Regency which took place in March 2017 until June 2017. This experiment was arranged in factorial Random Design Group (RAK). The first factor is manure consisting of 3 levels namely cow manure, goat and chicken, while the second factor is planting distance consisting of 3 levels that is 25 x 75 cm, 30 x 65 cm and 35 x 60 cm. the data were analyzed by using analytical variance followed by BNJ test at 5% confidence level. The result of the research shows the effect of interaction between manure and plant spacing on leaf number parameter, number of fruit per plant, number of fruit per hectare, wet weight of fruit, fruit weight per plant, fruit weight per hectare and harvest index of okra plant. The best treatment is the use of goat manure with spacing of 30 x 65 cm which produces the number of fruit per plant 4,67 pieces, wet weight of fruit 33,22 gram, and productivity 8,06 ton.